2014
DOI: 10.1371/journal.pone.0105180
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Transcriptional and Post-Transcriptional Regulation of ESC Characteristics by Core Pluripotency Transcription Factors in Protein-Protein Interaction Networks

Abstract: The molecular mechanism that maintains the pluripotency of embryonic stem cells (ESCs) is not well understood but may be reflected in complex biological networks. However, there have been few studies on the effects of transcriptional and post-transcriptional regulation during the development of ESCs from the perspective of computational systems biology. In this study, we analyzed the topological properties of the “core” pluripotency transcription factors (TFs) OCT4, SOX2 and NANOG in protein-protein interactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 51 publications
2
10
0
Order By: Relevance
“…In our study, the highest concentration of IL-6 was observed in the supernatant from AT-MSCs and BM-MSCs, and the lowest was observed in SK-MSCs and SM-MSCs. These observations are in line with a study performed by Priciola et al[67] and by Li et al[69], which suggests that IL-6 is more efficiently produced by undifferentiated cells.…”
Section: Discussionsupporting
confidence: 93%
“…In our study, the highest concentration of IL-6 was observed in the supernatant from AT-MSCs and BM-MSCs, and the lowest was observed in SK-MSCs and SM-MSCs. These observations are in line with a study performed by Priciola et al[67] and by Li et al[69], which suggests that IL-6 is more efficiently produced by undifferentiated cells.…”
Section: Discussionsupporting
confidence: 93%
“…Due to its key roles in ESCs, SALL4’s interactions with transcription factors crucial for pluripotency have also been explored. Two independent studies, using unbiased approaches of affinity purification of Oct4 followed by mass spectrometry, identified Sall4 to be one of its binding partners in mouse ESCs 131,132 . Both approaches identified components of the NuRD complex, raising the possibility that Sall4 may bridge the interaction between Oct4 and this epigenetic repressor complex.…”
Section: Molecular Dissection Of Sall4 Functions In Cellsmentioning
confidence: 99%
“…Mounting evidence has shown that ESCs self-renewal is orchestrated by a variety of transcription factors, signaling molecules and RNA regulatory factors ( Huang et al, 2015 ; Abu-Dawud et al, 2018 ). Previous work has indicated that transcriptional and post-transcriptional modifications are important for the regulation of ESCs self-renewal ( Li et al, 2014 ). It has been reported that Oct4 and NANOG recruit LSD1 and bind to promoters of development-related genes, thereby controlling ESCs self-renewal by modulating H3K4 and H3K27 methylation ( Adamo et al, 2011 ; Whyte et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%